Kidney function and dementia risk in community-dwelling older adults: the Shanghai Aging Study - Wang, Mengjing (Alzheimers Res Ther, 2021)
BACKGROUND: Association between kidney dysfunction and dementia has been studied in western cohorts, but with inconsistent conclusions which may be due to the different measurements of kidney function. We aim to verify the hypothesis that lower levels of kidney function would be associated with increased risk of incident dementia in Chinese elderly. METHODS: One thousand four hundred twelve dementia-free participants aged 60 years or older from the Shanghai Aging Study were enrolled and followed up for 5.3 years on average. Glomerular filtration rate (GFR) was calculated by using combined creatinine–cystatin C CKD-EPI (Chronic Kidney Disease Epidemiology Collaboration) equation. Diagnoses of incident dementia and Alzheimer’s disease (AD) were established using DSM-IV and NINCDS-ADRDA criteria based on medical, neurological, and neuropsychological examinations to each participant. Cox proportional regression was used to analyze the association of baseline GFR(crcys) levels with incident dementia/AD, adjusting age, gender, education years, APOE-ε4, diabetes, hypertension, baseline Mini-Mental State Examination score, and proteinuria. RESULTS: A total of 113 (8%) and 84 (7%) participants developed dementia and AD. Comparing to participants with high GFR(crcys) (≥ 80 ml/min/1.73 m(2)), participants with low (< 67 ml/min/1.73 m(2)) and moderate GFR(crcys) (67 ≤ GFR < 80 ml/min/1.73 m(2)) had increased risk of incident dementia with hazard ratios (HRs) of 1.87 (95% CI 1.02–3.44) and 2.19 (95% CI 1.21–3.95) after adjustment for confounders, respectively. Low (HR = 2.27 [95%CI 1.10–4.68]) and moderate (HR = 2.14 [95% CI 1.04–4.40]) GFR(crcys) at baseline was also independently associated with incident AD after adjustments when comparing to high GFR(crcys). The significant association between GFR(crcys) and dementia risk was observed in female but not in male participants. CONCLUSIONS: GFR(crcys) may be considered as a marker of an individual’s vulnerability to the increased risk of cognitive decline. SUPPLEMENTARY INFORMATION: Supplementary information accompanies this paper at 10.1186/s13195-020-00729-9.